The impact of within and between role experiences on role balance outcomes for working Sandwich Generation Women - Evans, Kiah; Millsteed, J.; Richmond, J.; Falkmer, Marita; Falkmer, Torbjorn; Girdler, Sonya (Informa Healthcare, 2018)
Women combining paid employment with dual caring responsibilities for children and aging parents, otherwise known as the sandwich generation, experience both benefits and costs related to role participation and quality of life. However, previous literature is inconclusive regarding the impact of this role combination on role balance. In the context of these mixed findings on role balance for working sandwich generation women, this study aimed to explore how within role characteristics and between role interactions are related to role balance for these women. This aim was achieved through the use of a questionnaire administered to 18 Australian working sandwich generation women. Data were analyzed using descriptive statistics and correlation coefficients, with findings suggesting the women studied tended to experience neither role balance or role imbalance. Within-role characteristics, particularly within the mother and family member roles, were related to role balance. In addition, between-role conflict and role interactions involving either the home maintainer or family member roles had the greatest impact on role balance.